2020
DOI: 10.1002/adfm.201908715
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Control of Triplet Emission in Donor–Bridge–Acceptor Organometallics

Abstract: Carbene‐metal‐amides (CMAs) are a promising family of donor–bridge–acceptor molecular charge‐transfer (CT) emitters for organic light‐emitting diodes. A universal approach is demonstrated to tune the energy of their CT emission. A blueshift of up to 210 meV is achievable in solid state via dilution in a polar host matrix. The origin of this shift has two components: constraint of thermally‐activated triplet diffusion, and electrostatic interactions between guest and polar host. This allows the emission of mid‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 51 publications
(122 reference statements)
6
61
0
Order By: Relevance
“…to-planar triplet geometry [31,32] , which possesses relatively low symmetry, but decreases by a factor ~20 in the higher symmetry orthogonal configuration [15] , in line with theoretical prediction [24,33] . This dramatic reduction in direct S 1 -T 1 SOC is fully consistent with El-Sayed's rule and the fact that the states involved should have different spatial wavefunctions for the total (angular plus spin) momentum to be conserved.…”
Section: Energy Landscape For Direct and Reverse Intersystem Crossingsupporting
confidence: 87%
See 2 more Smart Citations
“…to-planar triplet geometry [31,32] , which possesses relatively low symmetry, but decreases by a factor ~20 in the higher symmetry orthogonal configuration [15] , in line with theoretical prediction [24,33] . This dramatic reduction in direct S 1 -T 1 SOC is fully consistent with El-Sayed's rule and the fact that the states involved should have different spatial wavefunctions for the total (angular plus spin) momentum to be conserved.…”
Section: Energy Landscape For Direct and Reverse Intersystem Crossingsupporting
confidence: 87%
“…A broad excited-state DoS may originate from both variations in molecular conformation, and from the relative polarisation of the environment around individual chromophores, which varies with their separation and relative orientation. [24] In amorphous films, these parameters are randomly distributed, resulting in a Gaussian distribution of polarisation-induced energy shifts. Normalised delayed emission kinetics with monoexponential fits to crystalline and amorphous CMA1 within the 5 -4000 ns time range.…”
Section: Time-resolved Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Even though high PLQE is available in neat films for CMAs, if a host matrix is not utilized, diffusion via DET to the fluorescent sites will be inevitable since the CMAs and fluorescent emitters are in close contact. [ 38 ] It was recently demonstrated that the adoption of appropriate substituents attached to fluorescent emitters for the separation of donors and acceptors is a useful method for suppressing DET since the likelihood of transfer varies exponentially with chromophore spacing. [ 39 ] In this work, CMA1, CMA4, rubrene, and TBRb (molecular structures shown in Figure 1a) are employed to explore the influence of steric bulk, introduced via t ‐butyl substituents, on DET efficiency between CMAs and fluorescent emitters.…”
Section: Resultsmentioning
confidence: 99%
“…Au-Cz has previously been shown to exhibit rapid singlet-triplet interconversion and high performance in OLED devices 25 leading to a significant interest in developing this framework of emitters. [26][27][28][29][30][31] On the basis of timeresolved electroluminescence (EL) and photoluminescence (PL) measurements, Di et al demonstrated for Au-Cz rapid ISC to triplets (B4 ps), and that CMA emission occurs almost entirely via a delayed-emission channel (B350 ns). 25 Importantly, the torsional motion around the bridge brings the Au-Cz to a (perpendicular) configuration showing a very small energy gap between the S 1 and T 1 states and very small oscillator strength, while the (co-planar) configuration shows a higher energy gap but also a higher oscillator strength.…”
Section: Introductionmentioning
confidence: 99%